True horror stories - Deary, Terry (New York, N.Y., U.S.A. : Puffin Books, 1996)
A collection of horror stories from around the world based on experiences which someone has claimed are factual.
Originally published: London : Scholastic Children's Books, 1993.
Keywords: Parapsychology -- Juvenile literature; Supernatural -- Juvenile literature; Supernatural; Ghosts